Fundamentals of Franchising - Barkoff, Rupert Mitchell (American Bar Association, 2015)
Fundamentals of Franchising, Fourth Edition is charged with useful definitions, practical tips, and expert advice from experienced practitioners. Written to help lawyers and nonlawyers alike, this practical guide examines franchise law from a wide range of practice specialties and viewpoints. Each chapter is written by experienced practitioners whose cumulative knowledge provides you with a well-rounded overview of franchise law and alerts you to issues that may require further research or expertise. Strengthen your understanding of key issues in franchise law, including:Trademark lawStructuring the franchise relationshipFranchise disclosure issuesFranchise registrationFranchise relationship lawsAntitrust lawInternational franchisingRepresenting franchiseesThis edition also covers disclosure requirements under the revised FTC Franchise Rule, provides a state-by-state summary of franchise and business opportunity registration and disclosure statutes, and summarizes state procedural requirements for termination or nonrenewal.